Personality Variables as Predictors of Facebook Usage. Issue 2 (April 2014) - Caci, Barbara; Cardaci, Maurizio; Tabacchi, Marco E.; Scrima, Fabrizio
This study investigates the role of personality factors as predictors of Facebook usage. Data concerning Facebook usage and personality factors from 654 Facebook users were gathered using a web survey. Using path analysis, the results showed Openness was a predictor of Facebook early adoption, Conscientiousness with sparing use, Extraversion with long sessions and abundant friendships, and Neuroticism with high frequency of sessions. The possible role of Agreeableness in predicting low session frequency and friendships needs further validation.